Analysis of Tactical Knowledge for Learning an Alternative Invasion Sport - Olga Calle; Antonio Antúnez; Sergio José Ibáñez; Sebastián Feu (MDPI AG, 2024)
The study of declarative and procedural knowledge in sport allows us to assess students' tactical learning processes. The aim of this study was to analyze and compare the level of declarative and procedural knowledge acquired by students according to the pedagogical model and gender, after the application of two intervention programs for an alternative invasion sport, "Rosquilla". This study involved 136 students distributed into six groups of Primary Education (fifth and sixth year) and Secondary Education (first year). Each group in the same year participated in a different intervention program, one based on the Game-Centered Model and the other on a hybrid model of the Game-Centered Model and the Sports Education Model. A descriptive analysis was carried out to determine the characteristics of the participants. Subsequently, an independent samples Mann-Whitney U-test was applied to compare the level of knowledge between the models and genders in the pre- and post-test periods. A Linear Mixed Model was used to analyze the level of knowledge of students within each group and compare them according to methodology and gender. The results indicate that both programs generated improvements in declarative and procedural knowledge. Therefore, students learn equally regardless of the methodological perspective and gender.